Association Between Medicare Summary Star Ratings for Patient Experience and Clinical Outcomes in US Hospitals. (March 2016) - Trzeciak, Stephen; Gaughan, John P; Bosire, Joshua; Mazzarelli, Anthony J
Objective: In 2015, the Centers for Medicare and Medicaid Services (CMS) released new summary star ratings for US hospitals based on patient experience. We aimed to test the association between CMS patient experience star ratings and clinical outcomes. Methods: We analyzed risk-adjusted data for more than 3000 US hospitals from CMS Hospital Compare using linear regression. Results: We found that better patient experience was associated with favorable clinical outcomes. Specifically, a higher number of stars for patient experience had a statistically significant association with lower rates of many in-hospital complications. A higher patient experience star rating also had a statistically significant association with lower rates of unplanned readmissions to the hospital within 30 days. Conclusion: Better patient experience according to the CMS star ratings is associated with favorable clinical outcomes. These results support the inclusion of patient experience data in the framework of how hospitals are paid for services.